FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN POLA MAKAN SIAP SAJI (FAST FOOD) PADA MAHASISWA PROGRAM STUDI ILMU KESEHATAN MASYARAKAT STIKes HANGTUAH PEKANBARU - LPPM Al-Insyirah (Al Tamimi Kesmas: Jurnal Ilmu Kesehatan Masyarakat (Journal of Public Health Sciences), 2016)
Fast food is food available in quick time and ready, a kind of food packed , easily served , practical as fried chiken , hamburgers or pizza and in the form of a side dish pauk in packs instant noodles , canned sardines , nuggets , or also corn flakes as food for breakfast. Consume fast food if consumed in the number of many not good for the long term can trigger the emergence of various disease, like diabetes and coronary heart, hypertension. The effect cannot be felt in the short term but in the near term a long. This research is to find out what connected diet of fast foods astudents IKM STIKes Hang Tuah Pekanbaru the year 2015. The kind of research this is observational analytic with the design cross sectional .Population in this study a total of 678 students , study sample this is a student prodi hpi in the second semester II, IV , and VI who a total of 153 .The sampling method of technique used was random sampling .The analysis used is univariat analysis and bivariat chi-square with the who uses a tool in the form of the questionnaire measuring ` Besed on the results ofresearch shows the majority of respondents having a pattern of eating junk 91 (59,9%), signitifikan relationship between knowledge and there are nutrition white a pettren of eating fas food (P value 0,000, POR= 4,340), attitude(P value 0,011, POR =2,475), pocket money (P value 0,025, POR= 2,651 ). The advice in this research was for college students STIKes Hang Tuah Pekanbaru join a seminar health and increase knowledge health by receive information health to understood from consume fast food.